MAKNA KONOTATIF DAN GAYA BAHASA DALAM LIRIK LAGU ALBUM TENTANG YANG TAK DIKATA KARYA COFFTERNOON - Saputra, Adi; Patriantoro, Patriantoro; Hanye, Paternus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is titled The Connotative Meaning and Languange Style In The Songâ€™s Lyrics Album Tentang Yang Tak Dikata By Coffternoon. Generally this research aims to describe meaning based connotative taste value as well as usage variety of language styles contained in the album Tentang Yang Tak Dikata by Coffternoon. Method used in this research is descriptive method according to the problem under study with qualitative research forms. The source of the data is 10 from 11 songs in the album Tentang Yang Tak Dikata by Coffternoon, and the data is words and phrases in which there is connotative meanings and various styles of language. The main technique used in this research is a documentary study technique, transcription technique, and data analysis technique. Based on these conclusions, kind of connotative meaning the most widely used contained in album Tentang Yang Tak Dikata by Coffternoon is a type good connotation meaning which amounts to 54, and the most dominant variety of language styles in album Tentang Yang Tak Dikata by Coffternoon is variety of comparative language styles which amounts to 80.Â Keywords: Album Tentang Yang Tak Dikata, Connotative Meaning, Languange Style